Assessment of Chemically Modified Lignocellulose Waste for the Adsorption of Cr (VI) (2019)
Chromium (Cr(VI)) presents carcinogenic and mutagenic effects in living beings. Biosorption is an alternative to conventional technologies for the treatment of waste water. The aim of this study was to assess the use of corncob and orange peels modified with citric acid and calcium chloride, respectively, for the removal of Cr(VI) using a batch system taking into account pH and particle size. Biomaterial were characterized using an elemental and chemical analysis, and FTIR, in which was evidenced the presence of hydroxyl, carbonyl and carboxyl groups, belonging to the cellulose and lignin that are attributed for the presence of active centers which intervene in the adsorption process. Adsorption experiments through batch system were performed using a solution of potassium dichromate at 100 ppm, 150 rpm, varying pH (2, 3, 4 and 6) and particle size (0.355, 0.5 and 1 mm). From de results was found that maximum removal percentage was obtained at pH 2 and particle size of 0.355 using corncob and orange peels. Final concentration of Cr(VI) was determined by using the standard method ASTM D1687-02 with 1,5-diphenylcarbazide at 540 nm. Adsorption kinetics and isotherms were assessed with the best conditions found, in which the experimental data was adjusted to the Pseudo-second order and Freundlich models, respectively. R2 value greater than 0.95 suggests that the process is controlled by a chemical reaction leading the formation of multilayers. The performance of the biomass in terms of q0 was found to be: corncob>orange peels>corncob modified>orange peels modified.